A Basin Analysis of the Wabigoon Area of Lake Agassiz, a Quaternary Clay Basin in Northwerstern Ontario - Sharpe, David; Pullan, Susan; Warman, Timothy (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1992)
ABSTRACTInformation from a wide range of sources is integrated in a basin analysis of the Wabigoon Basin, a Quaternary clay basin located on the Canadian Shield in northwestern Ontario. The basin sediments were deposited between 10.9 ka and 9.5 ka, along the margin of the Rainy Lobe of the Laurentide Ice Sheet, which formed the northern boundary of proglacial Lake Agassiz. The basin architecture is dominated by four major elements: end moraines, eskers, kames and a clay plain, all of which overlie irregular bedrock topography. End moraines, eskers and kames are composed mainly of a fining upward sequence of gravels and sands. The geometry of these sedimentary units, and their sedimentary structures indicates they were deposited mainly by high and low-density turbidity currents, on ice-marginal subaqueous outwash fans. Eskers contain a core of coarse gravel and sand deposited within subglacial meltwater conduits, overlain by subaqueous fan sediments deposited at the conduit mouth. Esker ridges were formed during conduit filling events and flanking deposits were formed when a conduit remained in use during ice-marginal retreat. Where conduits were shortlived, isolated subaqueous fans (kames) were formed. A depositional model is proposed which relates moraine formation to catastrophic releases of subglacial meltwater and sediment simultaneously along the entire margin of the Rainy Lobe. The clay plain forms a broad blanket of fine-grained, rhythmically-bedded sediment which obscures bedrock topography, and often buries esker and kame deposits. Seismic profiles and overburden drilling reveal deep (50-70 m) bedrock lows beneath the clay plain. These lows, oriented sub-parallel to the ice margin, acted as sediment traps, and were infilled by the deposits of underflows generated at the ice margin.